Relationship of Essentially Small Quasi-Dedekind Modules with Scalar and Multiplication Modules - Obaid, Inas Salman; Hussain, Mukdad Qaess; AbdulKareem, Darya Jabar (Iraqi Journal of Science, 2020)
Let be a ring with 1 and D is a left module over . In this paper, we study the relationship between essentially small quasi-Dedekind modules with scalar and multiplication modules. We show that if D is a scalar small quasi-prime -module, thus D is an essentially small quasi-Dedekind -module. We also show that if D is a faithful multiplication -module, then D is an essentially small prime -module iff is an essentially small quasi-Dedekind ring.